Spotting of over Speeding Vehicles and Controlling the Speed in Highways using MEMS Sensor - Sathesh M.E, M; Shanmugapriyan, J (International Journal of Engineering and Technology, 2018)
This Paper describes about the spotting of an over speed of a vehicle in highway and controlling the speed of a vehicle whenever there is an uneven Condition Occurred. And alert the speed offence to control room and toll gate, the devices like Controller, RFID reader, MEMS sensor, GSM&LCD are used. The System are controlled by a microcontroller, The Micro-Controller plays an important role to do a desired task. The controller obtains the MEMS sensor, which is used to sense speed of the vehicle, Vehicle has RFID tag when speed violation take place where RFID reader reads the tag and identify the vehicle and send the information through GSM module. We design a project in such a manner that it gives an alert signal to the driver if he does not react to that, than two condition occurred first speed is been controlled and other speed offence fine is send control room and toll gate whenever vehicle crossing its maximum speed limit.Â